Critical Ignition Conditions of Wood by Cylindrical Firebrands - Salehizadeh, Hamed; Hakes, Raquel S. P.; Gollner, Michael J. (Frontiers in Mechanical Engineering, 2021)
This study investigated the thermal conditions preceding ignition of three dense woody fuels often found on structures by firebrands, a major cause of home ignition during wildland-urban interface (WUI) fires. Piles of smoldering cylindrical firebrands, fabricated from wooden dowels, were deposited either on a flat inert surface instrumented with temperature and heat flux sensors or on a target fuel (marine-grade plywood, oriented-strand board or cedar shingles) to investigate critical conditions at ignition. The former provided thermal data to characterize the time before and at ignition, while the latter provided smoldering and flaming ignition times. Tests were conducted in a small-scale wind tunnel. Larger firebrand piles produced higher temperatures at the center of the pile, thought to be due to re-radiation within the pile. Ignition was found to be dependent on target fuel density; flaming ignition was additionally found to be dependent on wind speed. Higher wind speeds increased the rate of oxidation and led to higher temperatures and heat fluxes measured on the test surface. The heat flux at ignition was determined by combining results of inert and ignition tests, showing that ignition occurred while transient heating from the firebrand pile was increasing. Ultimately, critical ignition conditions from firebrand pile exposure are needed to design appropriate fire safety standards and WUI fire modeling.